Putting Trade Logistics Reform “on the Map” in Armenia - Gabrielyan, Gagik; Huria, Ankur; Nazaryan, Arsen (World Bank, Washington, DC, 2012)
Armenia did it through trade logistics reform - with help from International Finance Corporation's (IFC's) Armenia doing business reform and regulatory simplification project, launched in February 2009. The project team builds constructive relationships-including well-designed and consistent communication-with the Ministry of Economy, the customs service, and the private sector to identify key issues and challenges and to design and implement reform measures. A key element of this advice has been IFC's assistance in preparing a detailed import/export process map, used to guide trade logistics reforms. This smart lesson explains the project's design approach to trade logistics reforms in Armenia (which can be customized and implemented in other locations) and shares key lessons learned.